Intervenciones de enfermería en pacientes con SIDA basado en la teoría de Ruland y Moore - Rosa Selena, Lascano Torres (2021)
ABSTRACT The present bibliographic review had the purpose of determining nursing interventions, applicable in patients with AIDS, based on the theory of Ruland and Moore, a disease that represents the most advanced stage of HIV infection and is characterized by the appearance of some infections opportunistic or oncological linked to the virus. In addition, this condition leads to an impairment in the physical, social and psychospiritual sphere that affects the well-being of the patient and her family. 100 bibliographic sources from different databases were reviewed, in which aspects related to the subject were addressed; Inclusion and exclusion criteria were applied, finally considering all 77 bibliographic sources, of which 45 were used for the triangulation process; obtaining as essential coincidences of 13 authors for pain expression, 10 authors of experience of well-being; experience of dignity and respect 11; state of tranquility 4; proximity of relatives 6. Based on the results, diagnostic labels and interventions were determined with the NANDA-NIC taxonomy that could be used in this type of patients in relation to the Ruland and Moore model. Key Words: Acquired Immune Deficiency Syndrome, Nursing Theory, Nursing Care. Reviewed by: Lcda. Diana Carolina Chávez Guzmán English Professor. c.c. 0650037955